"The Early Bird Catches the Worm - First Mover Advantage through IoT Adoption for Indian Public Sector Retail Oil Outlets". Issue 4 (2nd October 2019) - Das, Sudip
ABSTRACT: This paper identifies the various significant factors that contribute to the Internet of Things (IoT) adoption at the Indian Oil Marketing Companies (OMCs') Retail Oil Outlets (ROO) and empirically tests the model of constituents for the same. The logistic regression analysis was applied, using a survey of 402 respondents, to predict the adoption of IoT at the OMCs' ROO. Using the 7 factors as predictors, the regression analysis output showed a significant impact from 5 factors-People, Technologies, Processes, Data Security, and Competitive Advantage. To transform the existing ROO into "smart pumps, and to fully realize the expected benefits from the investment in IoT, the OMCs' need to give increased emphasis to these 5 factors. It tests the applicability of the PolySocial Reality (PoSR) framework and Thing Theory at the OMCs' ROO extending the literature by incorporating 'processes' to the existent framework of people, devices and communication technologies within the IoT ecosystem. "Data Security" and "Interoperability" tie up these four components together enabling a seamless flow of digital data among them and empowering the organization to realize "competitive advantage"